Quantitative enzyme immunoassay and semiquantitative immunohistochemistry of oestrogen and progesterone receptors in endometriotic tissue and endometrium. - Bergqvist, A (1997)
BACKGROUND: The capacity of different tissues to respond to steroids has been evaluated mainly according to the concentrations of oestrogen (ER) and progesterone (PR) receptors, which may be assayed either in tissue homogenates or histochemically. These two principles have been used in different studies of endometriotic tissue, giving somewhat different results, probably because the tissue is heterogeneously mixed with fibrotic tissue and blood cells to various degrees. AIMS: To compare a quantitative and a qualitative, semiquantitative immunocytochemical assay for ER and PR in a heterogenous tissue (endometriotic) and a similar but more homogenous tissue (endometrium). METHODS: ER and PR concentrations were measured using enzyme immunoassay (EIA) and immunocytochemistry (ICA) in the same tissue samples (endometriotic tissue from 31 women and endometrium from 19 of the same women). RESULTS: There was a significant correlation between PR concentration (using EIA) and semiquantitation of PR using PRICA in endometrial epithelium (p = 0.028). The correlation between the two techniques for ER concentration was not significant. In endometriotic tissue no correlation was found between the two techniques for ER or PR. CONCLUSIONS: These data show that in heterogeneous tissues like endometriotic tissue different techniques for measuring steroid receptors may produce substantially different results. The two techniques (EIA and ICA) are complementary and a combination of the two techniques might aid in determining optimal treatment.